Managing acidic mine water pollution in karst regions based on hydrogeological structures - Ren Hujun; Zhang Min; Li Xibin; Wang Hao; Yu Jinfeng; Zhou Chang (Results in Engineering)
Acidic mine drainage (AMD) is one of the primary pollutants from abandoned mines. This type of pollution is characterized by its extensive area, prolonged duration, and challenging detection process, especially in karst region with intricate hydrological systems, thereby posing a significant threat to the sustainable development of the economy. This paper focuses on the pollution of acidic mine water in the karst region of Southwest China and adopts a comprehensive watershed pollution management strategy. Considering the unique hydrogeological structure of the karst mines, the active water cycle, and the sensitivity and fragility of the ecological environment, this study proposes a set of acid mine drainage pollution control methods based on hydrogeological structures. These include “zonal management, one policy per mine; source control, pollution reduction; and end-of-pipe treatment, standard discharge.” This study applies coal mine water prevention and control techniques to environmental management, developing a series of source control methods including “filling, isolating, blocking, intercepting, draining, and controlling”. It also integrates physical, chemical, and biological methods for the end-of-pipe treatment of acidic mine water. This approach has been successfully applied to the management of acidic mine drainage in the Yudong River basin in Kaili, Guizhou. Long-term monitoring of the ''three-fields and four-water” revealed that rainfall significantly influences mine water quality. The study identified a “U-tube effect” whereby mine water exacerbates the pollution of karst water, leading to the development of a comprehensive prevention and control strategy termed the “three blocking (obstruction) and one guarantee” project. A comparative analysis of total iron content in the basin before and after treatment demonstrated a marked reduction, from 97.8mg/L to less than 0.3mg/L. This study provides a typical example for the prevention, control, and management of acid water pollution in karst areas across the watershed, and can serve as a reference for similar pollution management efforts.